ChemInform Abstract: Scalable C—H Oxidation with Copper: Synthesis of Polyoxypregnanes. Issue 17 (April 2016) - See, Yi Yang; Herrmann, Aaron T.; Aihara, Yoshinori; Baran, Phil S.
Abstract: The site‐specific steroidal C‐12 functionalization utilizing the Cu‐mediated Schoenecker oxidation is reinvestigated and dramatically improved using a new imine directing group in the substrates and alternative reducing agents.